From the observation to the construction of an urban dynamics simulation model: an inductive approach - Cécile Tannier; Pierre Frankhauser (Cybergeo)
In this paper, we chose to present a modelling concept, the aim of which is the simulation of intra-urban location dynamics. This concept includes some characteristics which relate it to the synergetic models as well as to the micro-simulation ones. In the first part of this paper, we describe and examine the modelling concept to focus in a second part on a more detailed presentation of one aspect of the model concerning the measure of the attractiveness of the neighbourhoods of a town.